The association of health literacy and eHealth literacy with caring concepts among carers of people with dementia - Efthymiou, Areti Christina (Cyprus University of Technology, 2020)
During these two last decades, there is an increase in health technological advances. Making them accessible to groups with vulnerability is a priority for educators and health care professionals. Access to web-based services could facilitate the informal carers of PwD in their everyday life. Carers of PwD are facing the consequences of the burden of care, feelings of anxiety, depression, guilt, make higher use of antidepressants and are more vulnerable to infections than the general population. Web-based services for informal carers may include training platforms and diseasespecific websites, forums, social networks and other interactive services, telehealth, telemedicine, applications for support and cognitive rehabilitation. The offer and demand for these services are differentiated among European countries. They are influenced by the digital skills and attitudes of the population towards technology. Health Literacy (HL) and eHealth literacy (eHL) are two concepts that can facilitate carers to search, find, assess and apply information related to dementiaspecific issues from different resources (friends, family, neighbours, health professionals, internet). This study investigates the level of HL and eHL and the associations with other caregiving variables. The study used a descriptive correlational study design and the methodology followed 5 phases. Initially, two scoping and two literature reviews organised to identify available research. Secondly, tools not available in Greek or for the specific population of carers were validated. The third phase included the consensus meeting on the terminology of eHealth Literacy and Health Literacy. Then, the pilot and the full-scale study followed. In total, 174 primary carers of PwD, (76% women, n=132) and 67 secondary carers (family, friend or neighbour who provide support to the primary carer and to the care-recipient), participated in a descriptive correlational study. Primary carers completed a face to face survey for the level of HL, eHL, internet use, dementia-specific internet use, caregiving self-efficacy (SE), coping strategies, caregiving perceptions and social support. Secondary carers completed the survey for HL, eHL and demographics. In this study, primary carers report a high level of eHL (29.21/40, SD=4.8) and HL (13.64/16, SD=1.92). The above is also the case for the secondary carers (eHL=30.54/40, SD=4.34 and HL=13.09, SD=2.05). The cluster analysis presented with 3 carers’ profiles: 1) carer with High HL, eHL and SE 2) carers with problematic coping and negative caregiving attitudes 3) carers with High HL, eHL and a strong Social Network. Carers with higher HL were more likely to report higher score of eHL, SEOR and SE-BM. Carers with higher eHL were more likely to report higher score of positive perceptions towards caring and emotion-focused coping. Carers of PwD in this sample, report an adequate level of HL and eHL, as they may act on behalf of the care-recipient. Services designed to meet the needs of a population with this HL and eHL profile could assist in the sustainability of the web-based services. Furthermore, nurses and other health care professionals if they obtain the tools to identify informal carers with low HL, could provide more tailored services according to carers’ needs and enhance their HL skills.
Keywords: eHealth; Dementia; Health Literacy; Self-efficacy; Carers; Coping; Social support; eHealth, άνοια; Εγγραμματοσύνη σε θέματα για την υγεία; Αυτό- αποτελεσματικότητα; Φροντιστές; Στρατηγικές αντιμετώπισης; Κοινωνική στήριξη